Identification of structural entities in NdF_3-LiF melts with cryoscopic method - 胡宪伟 王兆文 高炳亮 石忠宁 刘凤国 包莫日根高娃 (Transactions of Nonferrous Metals Society of China, 2010)
Nd-F species in NdF3-LiF melts were studied using cryoscopic method.Liquidus temperatures of melts of various compositions were determined by differential thermal analysis（DTA）.Based on the different model calculations,NdF4- was identified as the most likely Nd-F entity in the melts in which the mole fraction of NdF3 was lower than 20%,considering only one single Nd species in the melt,and which was formed in accordance with Temkin model or Flood model.Then,activities of different components in the melts were researched.The results show that activity of LiF decreases,and that of NdF3 increases with increasing the mole fraction of NdF3.The value of activity coefficient of NdF3 is higher than 1,and that of LiF is lower than 1.